Neutrophil Extracellular Traps Reprogram IL-4/GM-CSF-Induced Monocyte Differentiation to Anti-inflammatory Macrophages - Guimarães-Costa, Anderson B.; Rochael, Natalia C.; Oliveira, Fabiano; Echevarria-Lima, Juliana; Saraiva, Elvira M. (Frontiers in Immunology, 2017)
Monocyte-derived dendritic cells (mo-DCs) are essential for the development of a Th1 protective immune response against Leishmania parasites. It is well known that IL-4 and GM-CSF drive differentiation of human monocytes to dendritic cells (DCs). Here we investigate if Neutrophil Extracellular Traps (NETs) disrupts this process. NETs enriched supernatants, generated after human neutrophil activation by Leishmania promastigotes, were added to monocytes and differentiation monitored by expression of molecules associated with macrophage and DCs phenotypes, cytokine production and parasite killing. We found that NETs addition to IL-4/GM-CSF-treated monocytes prevented then to fully differentiate into DCs. No effect was observed if NETs were treated with DNase or by filtering the traps. Moreover, NETs closely interact with monocytes and downregulate the expression of the IL-4 receptor, which in turn disrupts fully differentiation of monocytes into DCs. Neutrophil elastase inhibition rescues the monocytes to DCs differentiation. Monocytes cultured with IL-4/GM-CSF and NETs differentiated into macrophages, as observed by the increased expression of CD68, CD32 and CD163, and decreased expression of CD80. Moreover, NET addition to IL-4/GM-CSF-treated monocytes rendered these cells less efficient to kill Leishmania parasites. Altogether, our results show that NETs interfere with IL-4/GM-CSF driven differentiation, reprograming the generation of mo-DCs to an anti-inflammatory macrophage.